Pembelajaran Pedagogik Spiritual melalui Kearifan Lokal - Masbur Masbur (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Learning is a concept of two dimensions of activity, namely learning that needs to be planned and updated, and directed to mastering a number of competences as an image of learning outcomes. This article aims to reveal the influence of local wisdom and spiritual learning. With local wisdom-based education, we can optimize the creation of education that can make sense of Indonesian human life. It means education will then be able to become a spirit that can color Indonesian human dynamics forward. The research method used in this study is the method of content analysis/meta analysis. Content Analysis is a study that combines the results of many original, systematic, planned studies, retrospective observations, with formal statistical analysis. The results of this study found that spiritual learning is one of the factors that influence the behavior of educated participants alongside other factors such as the intellectual, emotional, environmental, cultural and personal abilities of students. Humans have a spirituality to achieve a healthier self-development because we have that potential. This spiritual pedagogic, invites teachers to practice this value in learning activities that are mixed with local awareness of educated participants. Local origins that have spiritual values are explored and practiced in the learning process.